PEMIDANAAN MAKSIMAL PELAKU PENYIKSAAN HEWAN (SEBAGAI BENTUK PERLINDUNGAN TERHADAP HEWAN DAN ORANG-ORANG DISEKITAR PELAKU) - Nadia Ravita (2023)
This study aims to find out the application of law enforcement in cases of crimes of animal abuse in Indonesia today and the application of law enforcement which is oriented towards reducing the number of violence against animals in Indonesia and with the aim of cases like this getting proper law enforcement and rewards that have a deterrent effect for perpetrators. and can become a big problem in the future. This study uses a normative juridical research method which is interpreted as an approach that is carried out by searching by reviewing literature, theory and legal principles related to this research and data collection is carried out from the results of field reality information on the side of the resource person who is the head of the Shelter as well as an animal protection activist who often assisting cases of animal abuse and the Police Office in cases of animal abuse in Indonesia. Research has found that many studies from various countries of violence perpetrated on animals can result in things that are much more serious and are considered as the initial problem of other problems that will arise, law enforcement on animal abuse is still difficult to implement and has not been evenly distributed in a fair and law enforcement manner. it is mandatory to carry out psychiatric tests on all perpetrators of animal abuse cases in order to protect the environment around the perpetrators.